Przekłady literatury polskiej na język francuski jako próba ustalania kanonu – reinterpretacja i reintegracja w systemie literackiej kultury francuskiej - Warchoł, Jadwiga (Postscriptum Polonistyczne, 2020)
The author poses the question whether Polish literary canon that has been established since Romanticism through translations into French can be used in the joint‑creation of the canon of European literature. Methodology used by the author is based on translatological theory of polysystem by I. Even‑Zohar: it underlines the function of the translation in the target cultural system. The conclusions concerning establishing Polish literary canon in France are based on analyzing a series of examples, using the typical for French culture idea of what is „classic” and encyclopaedic tradition of popularizing general knowledge („culture générale”). From 19th century till the turn of 20th and 21st centuries the canonic Polish authors in France have become: A. Mickiewicz and C. Miłosz (in poetry), H. Sienkiewicz and W. Gombrowicz (in prose), Witkacy, Mrożek, Kantor (in drama), S. Lem (in science‑fiction literature) and R. Kapuściński (in reportage).